Relativistic treatment of scattering of electrons and positrons by mercury atoms. (2nd September 2019) - Haque, M. M.; Haque, A. K. F.; Bhattacharjee, Prajna P.; Uddin, M. Alfaz; Patoary, M. Atiqur R.; Basak, A. K.; Maaza, M.; Saha, B. C.
ABSTRACT: With a complex optical potential, V ( r ), the Dirac relativistic equation is solved, employing the partial wave technique, to evaluate the differential, integrated, momentum transfer and viscosity cross-sections for the elastic scattering of e ± -Hg system over the incident energy range of 1.0 eV ≤ E i ≤ 10.0 keV. We also calculate the inelastic and grand total cross sections for this system over the same energy range. The real part of V ( r ) includes the static, the exchange and the polarisation components while the imaginary component incorporates the absorption of particles into various inelastic channels. A detailed comparison of our results with experimental and other theoretical findings show a good overall agreement throughout the studied energy range, apart from some discrepancies at lower energies < 10  eV. GRAPHICAL ABSTRACT: